Differentiated Treatment for Acute Respiratory Distress Syndrome Induced by Direct and Indirect Etiological Factors - V. V. Moroz; A. V Vlasenko; A. M. Golubev; V. N. Yakovlev; V. G. Alekseyev; N. N. Bulatov; T. V. Smelaya (Общая реаниматология)
Objective: to study the efficiency of respiratory, non-respiratory, and pharmacological treatments in patients with acute respiratory distress syndrome (ARDS) induced by direct (aspiration pneumonitis, bilateral pneumonia, or lung contusion) and indirect (abdominal sepsis, polytrauma, or hemorrhagic shock) damaging factors. Subjects and methods. The results of treatment were retrospectively analyzed in 185 patients (122 men and 63 women whose age varied 18 to 69 years) with ARDS resulting from aspiration pneumonitis, bilateral pneumonia, or lung contusion (84 patients, including 53 men and 31 women) or from abdominal sepsis, polytrauma, or hemorrhagic shock (101 patients, including 69 men and 32 women). The efficiency of a lung opening maneuver, mechanical ventilation in the prone position, Surfactant BL, perftoran, and their combination use in ARDS developing due to direct and indirect damaging factors was studied. Results. The study treatment modalities were ascertained to show varying clinical efficiency in patients with ARDS caused by direct and indirect damaging factors. Conclusion. The findings made it possible to substantiate the necessity of setting off ARDS induced by direct and indirect damaging factors, to develop and propose new approaches to the differentiated treatment of different forms of ARDS. Key words: acute respiratory distress syndrome, direct damaging factors, indirect damaging factors, thoracopul-monary compliance, lung extravascular fluid, respiratory support, mechanical ventilation, positive end-expiratory pressure, lung opening maneuver, prone position, perftoran, surfactant.